Sennoside A+B Is as Effective as Polyethylene Glycol in Preparation for Small Intestine Capsule Endoscopy - Akın, Fatma Ebru; Yürekli, Öykü Tayfur; Tahtacı, Mustafa; Ersoy, Osman (Turkish Journal of Gastroenterology, 2024)
ABSTRACT Background/Aims: We aimed to compare the effectiveness of the polyethylene glycol (PEG) and sennoside A+B regimens after clear fluid diet and fasting in bowel preperation of capsule endoscopy. Materials and Methods: In this retrospective single-center study, patients who were consecutively examined with small bowel capsule endoscopy (SBCE) between May 2010 and March 2023 were evaluated. Patients who underwent PEG 4 L and sennoside A+B calcium 250 mL for small bowel preparation were assigned. The quality of the small bowel cleaning and the diagnostic yield in detecting of small bowel lesions were compared. Results: Two hundred forty-two patients who underwent SBCE for various indications (PEG 74.4%, sennoside A+B 25.6%) were included in the study. The mean proximal small bowel cleaning scores was 1.97 ± 0.77 for PEG and 1.98 ± 0.04 (P = .83) for sennoside A+B; the mid small bowel cleaning scores was 1.76 ± 0.84 for PEG and 1.59 ± 0.05 (P = .108) for sennoside A+B; the mean distal small bowel cleaning scores was 1.27 ± 0.08 for PEG and 1.3 ± 0.54 (P = .805) for sennoside A+B; and the total small bowel cleaning scores was 1.66 ± 0.06 and 1.62 ± 0.04 (P = .622) for PEG and sennoside A+B, respectively. There were no significant differences regarding small bowel cleaning scores both segmentally and totally. At the same time, the diagnostic value of SBCE was similar in both groups. Conclusion: The effectiveness of sennoside A+B in SBCE preparation is similar to that of PEG and can be used in intestinal cleansing. Cite this article as: Akın FE, Tayfur Yürekli Ö, Tahtacı M, Ersoy O. Sennoside A+B is as effective as polyethylene glycol in preparation for small intestine capsule endoscopy. Turk J Gastroenterol. 2024;35(5):360-365.